HUBUNGAN KEANEKARAGAMAN BENTOS PADA KUALITAS PERAIRAN DI SUNGAI DOX IX KELURAHAN TANJUNG RIA KOTA JAYAPURA - Galu P. W. Utami (Universitas Cenderawasih, 2024)
This research was conducted in the waters of the Dok IX River from October to January 2018, to find out the relationship between benthic diversity and water quality in the Dox IX River, Tanjung Ria Village. Sampling was carried out at three stations. The sampling technique was carried out by purposive sampling. Data analysis was carried out using the Shannon Winer diversity index.The research results found six families, namely Neritidae, Chitonidae, Cycloneritida, Thiaridae, Pachychilidae, and Gecarcinucidae. The results of the diversity analysis show a value of 1.6 which is categorized as lightly polluted. The results of chemical - physical parameter measurements were pH 5.24-9.66, temperature 23°C-28°, brightness 20-50 cm, salinity 0.1 ppm, DO 0.59-8.09 mg/L. Keywords : Bentos, Water Quality, River, Tanjung Ria.